Utility of a self-regulated learning microanalysis for assessing learning during professional development. Issue 3 (28th April 2022) - Peters-Burton, Erin E.; Goffena, Jordan; Stehle, Stephanie M.
Abstract: A key process in the discipline of science is argumentation, which has recently been receiving more attention in K-12 classrooms. The purpose of this multiple case study was to concurrently examine self-regulated learning processes (SRL) and learning outcomes of three teachers in a professional development (PD) on argumentation in science to assess the relationship between types of learning processes employed by teachers and corresponding learning outcomes. Three teacher cases were selected based on variations in their self-efficacy for the PD, the type of schools in which they taught, and their experiences with argumentation in science. Teachers who were able to use SRL strategies had deeper learning outcomes and created lesson plans that engaged students in higher levels of argumentation. It was found that the SRL microanalysis was useful in eliciting learning processes for learners and provided opportunities for learners to be more aware of their SRL practices. Implications for this study include ways to measure learning processes and learning outcomes concurrently to provide more effective PD instruction.